Conservation within the multicultural context - Ekaterina Pasnak (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Art museums are presently an arena of multicultural exchange. The modern conservator must be aware of his or her own assumptions, the assumptions of the institution, and learn to adapt to the cultural assumptions of the audience, so as to increase public appreciation and attendance. In this paper, values of identity and views on art are discussed and illustrated with examples from South Asia, Norway and Russia.